Overview of the halal food control system in Malaysia. (August 2018) - Ahmad, Anis Najiha; Ungku Zainal Abidin, Ungku Fatimah; Othman, Mohhidin; Abdul Rahman, Russly
Abstract: Awareness of the complexity in the global food chain, combined with several major halal food issues and scandals, are an impetus for major changes in the halal food control system in Malaysia. Malaysia holds a special position in the global halal market as the first country that assigns a government agency to regulate its halal matters and certification. This article describes and discusses the system for halal food control in Malaysia as framed by five important components for an effective national food control system: halal food legislation; halal food management control; inspection; laboratory; and education, communication, and training. Significant improvement has been made on the system; however, a few issues and challenges persist.